Risk Management at the Regional Inspectorate of XYZ Regency - Pambudhi, Khrisna Kusumo; Tewu, Denny; Sunaryo, T. (Yayasan Ilomata, 2025)
The obligation of local governments to implement risk management has been established since the issuance of Government Regulation No. 60 of 2008 on the Government Internal Control System. The Regional Inspectorate of XYZ Regency, as one of the local government agencies in the field of supervision, is also required to manage risks to achieve the objectives outlined in its strategic planning document. This study analyzes the implementation of risk management at the Regional Inspectorate of XYZ Regency by examining both strategic and operational risks. The analysis begins with a business canvas review of the agency’s business processes. The purpose of this study is to identify the strategic and operational risks faced by the Regional Inspectorate of XYZ Regency and to determine the necessary risk mitigation measures to address these risks to an acceptable level. The research employs a qualitative descriptive method to collect primary and secondary data through interviews, observations, and document reviews. The results indicate the identification of two strategic risks based on objectives and programs, as well as thirteen operational risks based on activities outlined in the planning and budgeting documents of the Regional Inspectorate of XYZ Regency. Existing controls and risk mitigation measures are formulated to align with the specific characteristics of the identified risks. The findings of this study have implications for the enhancement of risk management practices at the Regional Inspectorate of XYZ Regency. By implementing a more systematic approach—encompassing comprehensive risk identification, analysis, evaluation, and treatment—the Inspectorate can strengthen its oversight function and improve governance quality.